Amundsen's route to the South Pole - Drewry, David John; Huntford, Roland (Polar Record, 1979)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

A new process for the utilization of Antarctic krill - Ellingsen, Trond E.; Mohr, Viggo (Process Biochemistry, 1979)
Keywords: NARE 1976/77; Sørishavet; biokjemi; krill; lyskreps; marinbiologi; plankton

Botaniske undersøkelser på Bouvetøya : om materialet som ligger til grunn og dets videre bearbeiding - Engelskjøn, Torstein (1979)
Keywords: Bouvetøya; NARE 1978/79; botanikk; ekspedisjoner

Investigations on krill (Euphausiacea) sampled during the Norwegian Antarctic Research Expedition 1976–1977 - Fevolden, Svein Erik (Sarsia, 1979)
Krill was sampled in the Weddell Sea, farther south than ever before, and off Bouvet-öya. Five species were found: Euphausia superba, E. crystallorophias, E. frigida, E. triacantha, and Thysanoessa macrura. E. superba and E. crystallorophias were the most abundant species north and south of 74° S respectively. Length frequency analyses suggest that E. superba from the inner Weddell Sea takes three years to reach maturity. This population differed in several aspects from the populations farther north. E. crystallorophias and T. macrura were registered south to 77°45′ S, the southernmost localisation investigated. The material gives no clear evidence whether these species take one or two years to reach maturity. Their spawning activity seems to start earlier in the season than for E. superba. E. frigida and E. triacantha were only-found off Bouvetöya. Continuous echosounder recordings revealed that the total abundance of krill in the southern parts of the Weddell Sea was low, as was also the abundance on the route between the South Orkney Islands and Dronning Maud Land.
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; Sør-Orknøyene; Sørishavet; Weddellhavet; dyreplankton; krill; plankton; zooplankton

Antarktisk krill : deteksjon - fangst - anvendelse; teknisk / økonomisk analyse - Fiskerstrand, Rolf (Universitetet i Trondheim Norges tekniske høgskole, Institutt for skipsprosjektering, 1979)
Keywords: Sørishavet; ekspedisjoner; fiskerier; krill; zooplankton; økonomi

Norsk fangst av antarktisk krill : teknisk/økonomisk analyse - Fiskerstrand, Rolf (Norges fiskerihøgskole, Universitetet i Trondheim, Norges tekniske høgskole, Institutt for marin prosjektering, 1979)
Keywords: Sørishavet; ekspedisjoner; fiskerier; historie; hvalfangst; krill; pelagisk; zooplankton; økonomi

The genus Thalassiosira: species with internal extensions of the strutted processes - Fryxell, Greta A; Hasle, Grethe Rytter (Phycologia, 1979)
Keywords: Sørishavet; diatomeer; marinbiologi; oseanografi

Melting of ice in sea water: a primitive model with application to the Antarctic ice shelf and icebergs - Gade, Herman G. (Journal of Physical Oceanography, 1979)
Steady-state conditions are assumed to exist everywhere in the case of melting of the underside of an infinite slab of ice floating in sea water. Basic transfer equations for heat and salt are established and solutions derived for the interior corresponding to given far field values of the temperature and salinity of the water. The solutions are discussed in the T-S diagram where the behavior is particularly simple. Determining parameters are the characteristic velocities ks/d and Ks/h, where ks and Ks are the molecular and turbulent diffusivities, respectively, of salt, d and h the thicknesses of the corresponding laminar and turbulent layers. Also the nonmelting/nonfreezing case is discussed and the determining parameter established. Application of the theory to the Ross Ice Shelf (Little America V) gives acceptable results with d = 2 × 10−3 m and Ks = 20 −30 × 10−4 m2 s−1. Analysis of the static stability of the melt water mixtures reveals that with ambient temperatures approaching 17°C, the stratification becomes unstable. Icebergs brought to tropical waters will cause melt water mixtures to intrude at subsurface levels. Finally, convection obtained in laboratory experiments with melting ice in sea water is reported to be in concordance with the theoretically derived stability criterion.
Keywords: Sørishavet; geofysikk; glasiologi; hydrologi; oseanografi

Scott and Amundsen - Huntford, Roland (Hodder & Stoughton, 1979)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; polarforskning; polarområdene

Prosessering av sonarbøyedata fra Antarktis - Hvidsten, Johannes (Universitetet i Bergen, Seismological Observatory, 1979)
Keywords: Antarktis; seismologi

Mesozoic palaeomagnetism in Vestfjella, Dronning Maud Land, East Antarctica - Løvlie, Reidar (Geophysical Journal of the Royal Astronomical Society, 1979)
Thermal and alternating field demagnetization of oriented samples of Mesozoic lava flows (200–230 Myr) and dykes (154–172 Myr) collected from seven nunataks within the Vestfjella region, Dronning Maud Land, revealed stable directions of magnetization of normal and reverse polarity. Directional distributions of both polarities define tight groups along the same palaeomagnetic axis. Depending on whether the regional westward dip of the lava flows originated prior to, or after the intrusive igneous phase, two or one, respectively, palaeomagnetic pole(s) can be estimated. Both poles, however, are in general accord with previous Mesozoic poles from East Antarctica.
Keywords: Dronning Maud Land; NARE 1976/77; geofysikk; geologi

Naturressurser i Antarktis: av særlig interesse for Norge - Mobæk, Are; Østgård, Jon; Børset, Erik; Karlsen, Bernt Stilluf; Larsen, Thor (Miljøverndepartementet, 1979)
Keywords: Antarktis; polarområdene; ressurser

Flow of Antarctic ice shelves between long. 29° E. and 44° W - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: Antarktis; glasiologi; innlandsis; isfront; isshelf; isstrøm; kalving

Ice-shelf underwater morphology - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: Antarktis; NARE 1976/77; ekspedisjoner; forskning; glasiologi; isshelf; morfologi

Plough marks in the Weddell Sea - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; forskning; havbunnen; oseanografi

Fluoride in Antarctic Krill (Euphausia superba) and Atlantic Krill (Meganyctiphanes norvegica) - Soevik, Torleif; Braekkan, Olaf R. (Journal of the Fisheries Research Board of Canada, 1979)
Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F−/kg fat free dry matter, compared with 570 and 750 mg F−/kg in raw and boiled muscle. Biological availability was measured in a chick assay, and showed fluoride in krill to be equally utilized as sodium fluoride added to the diet. Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F−/kg fat free dry matter, compared with 570 and 750 mg F−/kg in raw and boiled muscle. Biological availability was measured in a chick assay, and showed fluoride in krill to be equally utilized as sodium fluoride added to the diet. Key words: krill, red feed, deep sea prawn, fluoride.
Keywords: Sørishavet; biokjemi; forurensning; krill; marin biologi; miljøgifter; plankton

Trends and prospects for regimes for living and mineral resources in Antarctica - Sollie, Finn (Stiftelsen, 1979)
Keywords: Antarktis; politikk; ressurser

Trends and prospects for regimes for living and mineral resources in the Antarctic + discussion - Sollie, Finn (Law of the sea: neglected issues - proceedings, Law of the Sea Institute twelfth annual conference, October 23-26, 1978, The Hague, 1979)
Keywords: Antarktis; forvaltning; jus

De norske Antarktis-ekspedisjonene 1976-77 og 1978-79: biologiske undersøkelser på Bouvetøya og i havet - Sømme, Lauritz; Fevolden, Svein Erik (Det norske videnskaps-akademi. Årbok, 1979)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biologi; geografi

On the drift ice conditions in the Atlantic sector of the Antarctic - Vinje, Torgny E (The Norwegian Institute of Technology, 1979)
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; konferanse; oseanografi; sjøis